Conservation of gene order, structure and sequence between three closely linked genes in Drosophila melanogaster and Drosophila virilis. - Lyamouri, M.; Enerly, E.; Kress, H.; Lambertsson, A. (Gene, 2002)
In Drosophila melanogaster, the apparently unrelated genes anon-66Da, RpL14, and anon-66Db (from telomere to centromere) are located on a 5547 bp genomic fragment on chromosome arm 3L at cytological position 66D8. The three genes are tightly linked, and flanked by two relatively large genes with unknown function. We have taken a comparative genomic approach to investigate the evolutionary history of the three genes. To this end we isolated a Drosophila virilis 7.3 kb genomic fragment which is homologous to a 5.5 kb genomic region of D. melanogaster. Both fragments map to Muller's element D, namely to section 66D in D. melanogaster and to section 32E in D. virilis, and harbor the genes anon-66Da, RpL14, and anon-66Db. We demonstrate that the three genes exhibit a high conservation of gene topography in general and in detail. While most introns and intergenic regions reveal sequence divergences, there are, however, a number of interspersed conserved sequence motifs. In particular, two introns of the RpL14 gene contain a short, highly conserved 60 nt long sequence located at corresponding positions. This sequence represents a novel Drosophila small nucleolar RNA, which is homologous to human U49. Whereas DNA flanking the three genes shows no significant interspecies homologies, the 3'-flanking region in D. virilis contains sequences from the transposable element Penelope. The Penelope family of transposable elements has been shown to promote chromosomal rearrangements in the D. virilis species group. The presence of Penelope sequences in the D. virilis 7.3 kb genomic fragment may be indicative for a transposon-induced event of transposition which did not yet scramble the order of the three genes but led to the breakdown of sequence identity of the flanking DNA.